The Analysis of Benzoate in Deepika Sauce of Sejahtera Sentosa SME with Uv-Vis Spectrophotometry Method - Andini, Andini; Sari, Meiria Istiana; Sari, Mokh. Suseno Aji (JURNAL AGROINDUSTRI HALAL, 2024)
The food additives level of use, particularly benzoate as preservatives, must comply with Indonesian regulations to ensure food safety for consumers. This study is aimed to determine the benzoic compounds content and determine the levels of benzoic compounds in 6 types of sauce manufactured by Sejahtera Sentosa SME. The identification of benzoate compounds was carried out via FeCl3 which was characterized by the formation of a brown precipitate while determination of the benzoate compounds level was conducted via the UV-Vis spectrophotometry method at a wavelength of 274 nm. The results indicated that the six samples of Deepika Sauce A, B, C, D, E and F contained benzoate preservatives sequentially by 0.986 ; 0.943 ; 0.852 ; 0.635 ; 0.700 ; and 0.992 g/kg. The benzoate preservatives use in chili sauce samples does not exceed the threshold set in the Regulation of the Head of the Drug and Food Control Agency of the Republic of Indonesia Number 11 of 2019, namely 1 g/kg.